The role of category ambiguity in normal and impaired lexical processing: can you paint without the paint? - Lukic, Sladjana; Krauska, Alexandra; Yoshida, Masaya; Thompson, Cynthia K. (Frontiers in Human Neuroscience, 2023)
Many words are categorially ambiguous, and can be used as a verb (to paint) or as a noun (the paint) due to the presence of unpronounced morphology, or “zero morphology”. On this account, the verb “paint” is derived from the noun “paint” through the addition of a silent category-changing morpheme. Past studies have uncovered the syntactic and semantic properties of these categorially ambiguous words, but no research has been conducted on how people process them during normal or impaired lexical processing. Are these two different uses of “paint” processed in the same way? Does this morphosyntactic structure have an effect on online sentence processing? This study presents two experiments that investigate the effect of morphosyntactic complexity in categorially ambiguous words presented in isolation (experiment 1) and in a sentential context (experiment 2). The first experiment tested 30 healthy adults and 12 aphasic participants’ ability to process categorially unambiguous and ambiguous nouns and verbs, using a forced choice phrasal-completion task, in which individuals choose whether the or to is most compatible with target words. Healthy controls and individuals with fluent aphasia all showed: (1) a bias toward the base category in selection rates for the and to, where the was selected more frequently for words identified to be base nouns, and to was selected more frequently for base verbs, and (2) longer reaction times for ambiguous (over unambiguous) words. However, individuals with nonfluent agrammatic aphasia showed a base-category effect only for nouns, with chance performance for verbs. The second experiment, using an eye-tracking while reading paradigm with 56 young healthy adults, showed a reading time slowdown for derived forms (to paint) compared to their base-category counterparts (the paint) in sentence contexts. These findings suggest that categorially ambiguous words likely share a common root, and are related by zero-derivation, and that impaired access to the base-category (i.e., verbs to visit) precludes associated morphological processes and therefore the retrieval of the derived-category (i.e., nouns the visit) in agrammatic aphasia. This study provides insights into the theory of zero morphology, and the principles that need to be accounted for in models of the lexicon.